Monetary Policy in a Changing World - Miller, Ervin (Quarterly Journal of Economics, 1956)
Introduction, 23. — I. Some weak points in traditional monetary policies, 23; budgetary problems, 24; shortcomings in the use of interest rates as a disciplinary device, 28; the perversity of illiquidity and uncertainty, 30; excessive generality of effect, 32. — II. A monetary policy for today's world, 33; the place of consumer and real estate credit controls, 34; security reserve proposals, 38. — III. Conclusions, 42.